Kemampuan Bercerita Pada Anak Usia 5 Tahun: Kajian Psikolinguistik - Aprilia, Mia Nur (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study analyzes the ability to tell stories to children aged 5 years. The ability to tell stories in children will improve speaking skills, such as at the phonological, morphological, and syntactic levels. In addition to improving speech, we can see how structural errors occur in children aged 5 years. The data used in this study is a voice recording of a 5-year-old boy named Abizar. The purpose of this study was to determine the language development of children at the age of 5 years through storytelling, knowing word mistakes in children aged 5 years. The method used in this study is a qualitative method with naturalistic techniques. The ability to tell will produce sentences spoken by the child and find the factors that exist.